Skrining dan Intervensi Kesehatan Kardiovaskular melalui Praktik Interprofessional Collaboration di Kabupaten Sigi, Sulawesi Tengah: Cardiovascular Health Screening and Intervention through Interprofessional Collaboration Practices in Marawola Subdistrict, Sigi Regency - Anna Veronica Pont; Kadar Ramadhan; Indro Subagyo; Sugeng Nuradji; Metrys Ndama; Zainul Zainul; Junaidi Junaidi; Andi Fatmawati Syamsu; Fajrillah Kolomboy; Lisnawati Lisnawati; I wayan Supetran; Taqwin Taqwin; Mercy Joice Kaparang; Nurfatimah Nurfatimah; Christine Christine (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Cardiovascular disease is still the leading cause of global death and shows an increasing trend in Indonesia, including in semi-urban and rural areas such as Marawola District, Sigi Regency. Low health literacy and limited access to services are challenges in preventing and detecting this disease. This community service activity aims to improve early detection and promotive-preventive interventions of cardiovascular diseases through the Interprofessional Collaboration (IPC) approach. The implementation method involved seven villages with a target of 210 heads of families (321 individuals). Activities include coordination, socialization, health screening (blood pressure, blood sugar levels, cholesterol, BMI, and abdominal circumference), health education, and profession-based interventions (nursing, midwifery, nutrition, and sanitation). The screening results showed the prevalence of hypertension at 44.1%, pre-hypertension at 48.7%, diabetes mellitus at 11.5%, high cholesterol at 39%, and obesity and overweight at 43.6%. The collaborative intervention through education about the efforts of blood pressure and improved participants' understanding of nutrition, environmental cleanliness, and medication adherence. The discussion emphasized that the IPC accelerates problem identification, enriches interventions, and increases community involvement. However, limited time and laboratory equipment are obstacles that must be fixed in future activities. In conclusion, integrating IPC in community-based cardiovascular screening and intervention programs is feasible and sustainable.